2011
DOI: 10.3354/meps08914
|View full text |Cite
|
Sign up to set email alerts
|

Blue whale habitat selection and within-season distribution in a regional upwelling system off southern Australia

Abstract: Blue whales Balaenoptera musculus aggregate to feed in a regional upwelling system during November-May between the Great Australian Bight (GAB) and Bass Strait. We analysed sightings from aerial surveys over 6 upwelling seasons (2001-02 to 2006-07) to assess within-season patterns of blue whale habitat selection, distribution, and relative abundance. Habitat variables were modelled using a general linear model (GLM) that ranked sea surface temperature (SST) and sea surface chlorophyll (SSC) of equal importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 58 publications
6
110
0
Order By: Relevance
“…They also migrate annually between higher latitudes in the summer and lower latitudes in the winter and are believed to roam as far north as the northern Indian Ocean and Banda Sea [77]. The Perth Canyon (WA; [78,79]) and the Bonney upwelling (SA; [80]) are two notable feeding aggregations of pygmy blue whales.…”
Section: Balaenoptera Musculus-blue Whalementioning
confidence: 99%
“…They also migrate annually between higher latitudes in the summer and lower latitudes in the winter and are believed to roam as far north as the northern Indian Ocean and Banda Sea [77]. The Perth Canyon (WA; [78,79]) and the Bonney upwelling (SA; [80]) are two notable feeding aggregations of pygmy blue whales.…”
Section: Balaenoptera Musculus-blue Whalementioning
confidence: 99%
“…Whale distribution has been linked to oceanographic and bathymetric parameters in many areas of the world (Tynan et al 2005;Laran and Gannier 2008;Gill et al 2011) including Antarctic waters (Friedlaender et al 2006Ribic et al 2008;Ainley et al 2011;Williams et al 2014). For large baleen whales spending the summer months in the Southern Ocean, these parameters most likely serve as proxies for prey distribution, since feeding is the main reason for these species to perform seasonal migrations to Antarctic waters.…”
Section: Introductionmentioning
confidence: 99%
“…The large distances between the Kahurangi Point upwelling area and the majority of blue whale sightings presented here (50Á150 km) does not weaken this hypothesis. A spatial disconnect between upwelling centres and locations of euphausiid blooms with high rates of blue whale sightings has been documented in studies of blue whales off southern Australia (Gill et al 2011), Channel Islands, California (Croll et al 1998 and Monterey Bay, California (Croll et al 2005). All three of these studies reported increased sightings of foraging blue whales in association with dense concentrations of euphausiids that formed downstream of cold water coastal upwelling systems.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic aerial surveys, conducted at regular temporal intervals (e.g., monthly) can collect standardised data that will elucidate the spatial (how big) and temporal (how frequent and persistent) scale of blue whale distribution in the region (e.g., Gill et al 2011). The production of high intensity, low frequency and long duration acoustic calls is a common and important aspect of blue whale behaviour worldwide .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation